2011
DOI: 10.2215/cjn.06550810
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin and Dickkopf-1 in Renal Osteodystrophy

Abstract: SummaryBackground and objectives The serum proteins sclerostin and Dickkopf-1 (Dkk-1) are soluble inhibitors of canonical wnt signaling and were recently identified as components of parathyroid hormone (PTH) signal transduction. This study investigated the associations between sclerostin and Dkk-1 with histomorphometric parameters of bone turnover, mineralization, and volume in stage 5 chronic kidney disease patients on dialysis (CKD-5D). Design, setting, participants, & measurementsIn a cross-sectional study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
178
8
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(219 citation statements)
references
References 30 publications
25
178
8
8
Order By: Relevance
“…This finding is in agreement with results in non-CKD animals and patients showing lower bone formation with higher sclerostin levels (16,17,32). Also, in prior studies in CKD-5D patients, we found a strong negative correlation between sclerostin blood levels and bone formation parameters (38), which could explain why, prospectively, patients with CKD-5D and higher sclerostin lose more bone than patients with lower sclerostin levels. The baseline finding of a positive relationship between sclerostin and baseline BMD in CKD- Figure 1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in agreement with results in non-CKD animals and patients showing lower bone formation with higher sclerostin levels (16,17,32). Also, in prior studies in CKD-5D patients, we found a strong negative correlation between sclerostin blood levels and bone formation parameters (38), which could explain why, prospectively, patients with CKD-5D and higher sclerostin lose more bone than patients with lower sclerostin levels. The baseline finding of a positive relationship between sclerostin and baseline BMD in CKD- Figure 1.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, postmenopausal women treated with a sclerostin antibody were found to have a 5.3% increase in lumbar spine BMD (18). Sclerostin has been shown to be increased in CKD-5D patients (38). A strong inverse relationship was observed between GFR and serum sclerostin (39).…”
Section: Discussionmentioning
confidence: 99%
“…(32)(33)(34) Furthermore, serum levels of the Wnt/b-catenin antagonists, sclerostin (SOST) and Dickkopft-1 (DKK1), were recently reported to be elevated in individuals on dialysis compared to non-CKD individuals, raising the possibility that repression of the b-catenin signaling pathway may also occur in the setting of CKD. (69) The importance of b-catenin signaling on bone mass and remodeling has been well studied. In addition to regulation of osteoclast activity, b-catenin signaling promotes osteogenesis of mesenchymal stem cells, increased osteoblast proliferation, mineralization, and decreased osteoblast apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of CJASN, Cejka et al (18) hypothesize that sclerostin, a protein expressed by osteocytes, may play an important role in ROD, on the basis of the results of a cross-sectional bone biopsy study done in 60 patients who had stage 5D CKD and were on long-term hemodialysis treatment. Sclerostin is the gene product of SOST, discovered in 2001 (19).…”
mentioning
confidence: 99%
“…Interestingly, Cejka et al (18) found an inverse relation between serum sclerostin and intact PTH (iPTH). Moreover, sclerostin was a strong predictor of bone turnover and osteoblast number.…”
mentioning
confidence: 99%